An investigation into the preparation of carbon black by partial oxidation of spent tyre pyrolysis oil. (1st January 2022) - Onyeka Okoye, Chiemeka; Zhu, Mingming; Jones, Isabelle; Zhang, Juan; Zhang, Zhezi; Zhang, Dongke
Graphical abstract: Highlights: Carbon black (CB) was successfully prepared from spent tyre pyrolysis oil. The CB properties are comparable to those of commercial CB products. CB yield is determined by reaction temperature and residence time. CB quality is determined by reaction temperature and oxygen concentration. Hydroxyl, carbonyl and carboxyl are major surface functional groups. Abstract: To promote the use of recycled waste materials as an industrial feedstock, this study examined the preparation of carbon black (CB) by partial oxidation of a spent tyre pyrolysis oil using a drop tube furnace. The effect of reaction temperature, the residence time of gas in the reactor and inlet gas oxygen concentration on the yield and properties of the CB were evaluated. The surface chemistry, chemical composition, morphological and thermal properties of the CB samples were characterised using XPS, EA, TEM, BET, and TGA, respectively. The CB yield increased with increasing reaction temperature but decreased as the residence time or oxygen concentration increases. The CB primarily consisted of C (90.5–98.6%) and O (0.9–7.4%), with small traces of S (<1%), Si (<1%) and H (<2%). Hydroxyl, carbonyl, and carboxyl are the key functional groups found on the CB surface, with the hydroxyl groups being dominant. The CB were highly graphitic with a lattice spacing in the range of 0.338–0.350 nm and had BET surface areas of 4–22 m 2 g −1 . The mean primary particle size ranged from 92 to 176 nm and decreased with increasing reaction temperature and oxygen concentration. The CB aggregate configuration became more complex with increasing reaction temperature, residence time and oxygen concentration. The results were not only comparable with commercial CB products from fossil fuel feedstocks but are expected to provide the needed motivation to move towards circular economy strategies, which have positive impacts from a sustainability perspective.